Amanah Ikhtiar Malaysia’s Credit-based Povety Alleviation Programme. - Omar, Mohamed Zaini; Hassan, Fatimah (Nanyang Technology University, 2006)
The formulation and implementation of the First Five year Development Plan (1956-1960) marked the origin of rural development planning in Malaysia.